The role of corporate governance in crisis management : evidence from Nordic financials following the Covid-19 crisis - Luoma-Halkola, Pauliina (2023)
This master’s thesis evaluates whether there is a relationship between the corporate governance ratings of Nordic financials and their ability to navigate through the COVID-19 crisis. The aim of this thesis is to analyze the Nordic corporate governance model and its connections to the organizations’ crisis management capabilities. The study utilizes a linear regression model to assess the relationship between the independent variable of governance score rating, and two alternative dependent variables of financial ratios ROA and ROE. The corporate governance ratings of the sample companies have been extracted from the independent ESG-rating provider Institutional Shareholder Services. ROA and ROE are captured as YoY changes between 2019 and 2020 when the pandemic emerged. This YoY ratio indicates how much negative events impacted the sample companies’ profitability. Furthermore, the YoY differences in ROA and ROE between 2020 and 2021 are also utilized as alternative dependent variables to evaluate whether the corporate governance rating of the company had an impact on how quickly the corporations started recovering from the crisis caused by the pandemic. According to the empirical findings of this thesis, the corporate governance rankings are not linked to the companies’ ROA and ROE developments during and after the COVID-19 shock, although coefficients for ROA were significant. However, this does not mean that the linkage does not exist. Therefore, this thesis calls for further research on the impacts of good corporate governance practices in crisis management. Additionally, the new regulatory developments in the field of ESG will make new studies on ESG-rating divergence relevant during the upcoming years.